Metoda oceny rynkowych szans nowego produktu - Iwasiewicz, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper describes a new method of estimation of the price and marketing quality level of its new product, for the estimation of its market chances. This method needs information about prices and marketing quality level of substitutes and information about consumers budget constraints. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 193-205